KONSEP VALUE FOR MONEY DALAM MENGUKUR KINERJA PELAYANAN SEKTOR PUBLIK - Agustin, Risa Dwi; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out the concept of value for money which is measured by Report onAccountability and Performance of Government Institutions (LAKIP) in 2015 at Revenue and FinancialManagement Offices City of Surabaya. This research is a qualitative descriptive research. The data collectiontechnique has been conducted by using observation, documentation, and interview. The performance indicatorsmeasures 3 (three) main elements in the value for money concept i.e. economy, efficiency, and effectiveness. Theresult of the research of the Report on Accountability and Performance of Government Institutions(LAKIP) City of Surabaya shows that It can be stated that the economy aspect can been seen from theprocurement of office goods and services in which the budget fund which has been used to run this activity is91.6%. The efficiency aspects can be seen from the intensification and the extension activities of local tax byusing 86.45% of the available budget. The effectiveness can be seen from the achievement of local tax which hasgenerated as many as 102.22%. Therefore, the outcome is more than 100% and it can be stated effective.Keywords: Value for Money, Economy, efficiency, effectiveness, outcome.